Faktor Penentu Minat Karier Mahasiswa Akuntansi Lembaga Keuangan Syariah - Ashliana; Mochammad Arif Budiman (Indonesian Journal of Applied Accounting and Finance, 2025)
This study aims to analyze the effect of knowledge, apprenticeship, work environment, religiosity, and financial rewards on students’ interest in choosing a profession. This research uses a quantitative approach with survey data collected from 198 students of the Islamic Financial Institutions Accounting Study Program at Banjarmasin State Polytechnic. The findings indicate that, partially, knowledge, work environment, and financial rewards have a significant effect on student interest, while apprenticeship and religiosity do not show a significant influence. Simultaneously, all variables—knowledge, apprenticeship, work environment, religiosity, and financial rewards—have a significant effect on students’ interest in selecting a profession, indicating that both individual and external factors play an important role.